New secoiridoid ester of swertiamarin and secoxyloganic acid with hepatoprotective activity from Centaurium spicatum L. - Ahmed E. Allam; Alaa M. Nafady; Mohamed A. El-Shanawany; Fumide Takano; Tomihisa Ohta (Journal of Pharmacy & Pharmacognosy Research, 2015)
Context: Centaurium spicatum (L.) Fritsch (Gentianaceae) is an annual herb occurring in Southern Europe and Northern Africa where it is used in traditional medicine for treatment of numerous illness.